Akreditasi Sekolah Menurut Persepsi Siswa : Studi di Sekolah Menengah Kejuruan (SMK) Negeri 1 Lubuk Sikaping - Eci Sarmila; Nurhizrah Gistituati (Universitas Negeri Padang, 2021)
This study aims to determine how appropriate the results of school accreditation are with the existing reality as seen from the students' perceptions. This type of research is descriptive quantitative. The population of this study were 480 class XI students at the Vocational High School (SMK) Negeri 1 Lubuk Sikaping, with a sample of 90 people who were determined using the Slovin formula. Sampling using proportional incidentil sampling technique. The research instrument used was a Likert Scale model questionnaire consisting of 36 items with alternative answers to Strongly Agree (SS), Agree (S), Disagree (KS), Disagree (TS), Strongly Disagree (STS). Before being used, the questionnaire is tested for validity and reliability first. The collected data is processed by looking for the average score and the average achievement level (TCR). The results showed that in general according to the accreditation students of Vocational High School (SMK) Negeri 1 Lubuk Sikaping, it was only in the appropriate criteria (not very suitable) between the rankings obtained and the existing reality, with a TCR of 81.18%. However, if it is observed per the measured aspect, then there is one aspect, namely the facilities and infrastructure, the accreditation according to the students is not very suitable or does not match the rank obtained with the existing reality, with a TCR of 79.33.